Evaluation of aluminum stress induced antibacterial and antifungal activities in Roman nettle - (:unkn) unknown (Parlar Scientific Publications, 2019)
In this current work, Roman nettle (Urtica pilulifera L.), a traditional medicinal plant that is very common and widespread species throughout Asia, Europe, and Northern Africa, was used as a model plant to investigate changes in antimicrobial activity following the application of aluminum stress. U. pilulifera seedlings were grown in growth-room conditions and 0, 100, and 200 μM AlCl3 were applied to the plants together with Hoagland solution (20 ml) for two months. The antimicrobial activities were tested against nine strains of bacteria (Salmonella sp., Staphyllococcus aureus, Escherichia coli, E. coli O157:H7 and Bacillus cereus) and fungus (Penicillum sp., Saccharomyces cerevisiae, Candida tropicans and C. albicans) by using the disc diffusion and agar well methods. The accumulated Al was measured by using ICP-OES in the leaves of studied plant samples. Additionally, a control group (water + 11.31 mg l-1 Al) was prepared and applied to selected bacteria and fungi in order to understand the reason for obtained antimicrobial activities of Roman nettle is whether because of the compounds isolated from nettle leaves exposed to Al stress, or Al itself accumulated in leaves. The data proved that inhibitory antimicrobial effects were altered in U. pilulifera upon the application of Al stress, especially on fungi species. © 2019 Parlar Scientific Publications. All rights reserved.
Keywords: Aluminum stress; Antimicrobial activity; Urtica pilulifera